Overlap between Parkinson disease and Alzheimer disease in ABCA7 functional variants. (February 2016) - Nuytemans, Karen; Maldonado, Lizmarie; Ali, Aleena; John-Williams, Krista; Beecham, Gary W.; Martin, Eden; Scott, William K.; Vance, Jeffery M.
Abstract : Objective: Given their reported function in phagocytosis and clearance of protein aggregates in Alzheimer disease (AD), we hypothesized that variants in ATP-binding cassette transporter A7 ( ABCA7 ) might be involved in Parkinson disease (PD). Methods: ABCA7 variants were identified using whole-exome sequencing (WES) on 396 unrelated patients with PD and 222 healthy controls. In addition, we used the publicly available WES data from the Parkinson's Progression Markers Initiative (444 patients and 153 healthy controls) as a second, independent data set. Results: We observed a higher frequency of loss-of-function (LOF) variants and rare putative highly functional variants (Combined Annotation Dependent Depletion [CADD] >20) in clinically diagnosed patients with PD than in healthy controls in both data sets. Overall, we identified LOF variants in 11 patients and 1 healthy control (odds ratio [OR] 4.94, Fisher exact p = 0.07). Four of these variants have been previously implicated in AD risk (p.E709AfsX86, p.W1214X, p.L1403RfsX7, and rs113809142). In addition, rare variants with CADD >20 were observed in 19 patients vs 3 healthy controls (OR 2.85, Fisher exact p = 0.06). Conclusion: The presence of ABCA7 LOF variants in clinically defined PD suggests that they might be risk factors for neurodegeneration in general, especially those variants hallmarked by protein aggregation. More studies will be needed to evaluate the overall impact of this transporter in neurodegenerative disease.